2011
DOI: 10.4161/bioa.1.4.17643
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear actin-related proteins take shape

Abstract: T he function of nuclear actin is poorly understood. It is known to be a discrete component of several chromatin-modifying complexes. Nevertheless, filamentous forms of actin are important for various nuclear processes as well. Nuclear actin is often associated with nuclear actin-related protein Arp4 and other actin-related proteins like Arp8 in the INO80 chromatin remodeler. We recently determined the crystal structure of S. cerevisiae Arp4 that explains why Arp4 is unable to form actin like filaments and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…It has been repeatedly reported that actin can interact with components of chromatin-remodeling complexes, modulating the activity of these complexes as a whole. For example, actin is present in chromatin-remodeling complexes BAF [39,40], INO80 [41,42], and SWR1 [43]. It is assumed that actin can regulate the function of the ATPase subunit in chromatin remodeling complexes and contributes to the recognition of extranucleosomal linker DNAs, forming a subcomplex with actin-related proteins [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been repeatedly reported that actin can interact with components of chromatin-remodeling complexes, modulating the activity of these complexes as a whole. For example, actin is present in chromatin-remodeling complexes BAF [39,40], INO80 [41,42], and SWR1 [43]. It is assumed that actin can regulate the function of the ATPase subunit in chromatin remodeling complexes and contributes to the recognition of extranucleosomal linker DNAs, forming a subcomplex with actin-related proteins [35].…”
Section: Discussionmentioning
confidence: 99%
“…Arp4 is present in the majority of all phyla and is predominantly a nuclear protein participating in chromatin-remodelling (Meagher et al, 2009;Dion et al, 2010;Fenn et al, 2011;Kast and Dominguez, 2011). Arp4 is also involved in transcription regulation (Harata et al, 2002;Jiang and Stillman, 1996), DNA repair (Van Attikum et al, 2004), histone acetylation (Galarneau et al, 2000) as well as kinetochore-spindle attachment, and gene silencing at centromeres (Minoda et al, 2005).…”
Section: Actin-related Proteins In Diatomsmentioning
confidence: 99%
“…Two other actin family members, Arp2 and Arp3, are known to facilitate actin polymerization in the cytoplasm and also in the nucleus [10,11]. The basal structures of Arps2/3 and -4 are highly similar to actin, and both bind to actin [6,24]. However, the former binds to the pointed end while the latter binds to the barbed end of an actin molecule [22].…”
Section: Arp4 Is Involved In Genome Functions As a Novel Suppressor Omentioning
confidence: 99%
“…Nuclear F-actin also plays various roles in the nucleus, including in transcriptional regulation [6]. For example, the formation of nuclear F-actin decreases the nuclear G-actin pool, causing activation of SRF target genes through the retention of MAL in the nucleus [4].…”
Section: Introductionmentioning
confidence: 99%